Imaging of Postoperative Infection at the Knee Joint - Taljanovic, Mihra S.; Gimber, Lana H.; Omar, Imran M.; Klauser, Andrea S.; Miller, Michael D.; Wild, Jason R.; Chadaz, Tyson S. (Seminars in Musculoskeletal Radiology, 2018)
Postoperative infections of the knee are uncommon but may occur with joint arthroplasties, fracture fixation, or after arthroscopic procedures. The ultimate diagnosis is made by joint aspiration or tissue sampling. Joint aspiration and tissue sampling can be performed under imaging guidance or intraoperatively. Imaging is an important adjunct to clinical and laboratory findings and should start with radiographs. Cross-sectional imaging including magnetic resonance (MR) imaging, computed tomography (CT), nuclear studies, and ultrasound (US) are frequently used if the diagnosis is in doubt and to evaluate the extent of disease. We discuss the current algorithm in the diagnosis of various postoperative infections of the knee joint. The article addresses the utility of radiography, MR imaging, CT, US, and the most commonly used nuclear studies in the diagnosis of various postoperative knee infections and the imaging appearances of these infections on each of these diagnostic modalities.
Keywords: knee; joint; postoperative; infection; imaging